Step
*
1
of Lemma
EquatePairs_wf
1. x : Base
2. y : Base
3. n : Base
4. m : Base
5. ¬(y = n ∈ Base)
6. ¬(x = m ∈ Base)
7. ¬(n = m ∈ Base)
⊢ ∀x1,y1,z:Base.
    (((x1 = y1 ∈ Base)
     ∨ (((x = x1 ∈ Base) ∧ (n = y1 ∈ Base)) ∨ ((x = y1 ∈ Base) ∧ (n = x1 ∈ Base)))
     ∨ (((y = x1 ∈ Base) ∧ (m = y1 ∈ Base)) ∨ ((y = y1 ∈ Base) ∧ (m = x1 ∈ Base)))
     ∨ ((x = y ∈ Base) ∧ (((n = x1 ∈ Base) ∧ (m = y1 ∈ Base)) ∨ ((n = y1 ∈ Base) ∧ (m = x1 ∈ Base)))))
    
⇒ ((y1 = z ∈ Base)
       ∨ (((x = y1 ∈ Base) ∧ (n = z ∈ Base)) ∨ ((x = z ∈ Base) ∧ (n = y1 ∈ Base)))
       ∨ (((y = y1 ∈ Base) ∧ (m = z ∈ Base)) ∨ ((y = z ∈ Base) ∧ (m = y1 ∈ Base)))
       ∨ ((x = y ∈ Base) ∧ (((n = y1 ∈ Base) ∧ (m = z ∈ Base)) ∨ ((n = z ∈ Base) ∧ (m = y1 ∈ Base)))))
    
⇒ ((x1 = z ∈ Base)
       ∨ (((x = x1 ∈ Base) ∧ (n = z ∈ Base)) ∨ ((x = z ∈ Base) ∧ (n = x1 ∈ Base)))
       ∨ (((y = x1 ∈ Base) ∧ (m = z ∈ Base)) ∨ ((y = z ∈ Base) ∧ (m = x1 ∈ Base)))
       ∨ ((x = y ∈ Base) ∧ (((n = x1 ∈ Base) ∧ (m = z ∈ Base)) ∨ ((n = z ∈ Base) ∧ (m = x1 ∈ Base))))))
BY
{ ((Auto THEN SplitOrHyps THEN ExRepD THEN SplitOrHyps THEN ExRepD)
   THEN Try (((OrLeft THENM Eq) THEN Auto))
   THEN OrRight
   THEN Auto) }
Latex:
Latex:
1.  x  :  Base
2.  y  :  Base
3.  n  :  Base
4.  m  :  Base
5.  \mneg{}(y  =  n)
6.  \mneg{}(x  =  m)
7.  \mneg{}(n  =  m)
\mvdash{}  \mforall{}x1,y1,z:Base.
        (((x1  =  y1)
          \mvee{}  (((x  =  x1)  \mwedge{}  (n  =  y1))  \mvee{}  ((x  =  y1)  \mwedge{}  (n  =  x1)))
          \mvee{}  (((y  =  x1)  \mwedge{}  (m  =  y1))  \mvee{}  ((y  =  y1)  \mwedge{}  (m  =  x1)))
          \mvee{}  ((x  =  y)  \mwedge{}  (((n  =  x1)  \mwedge{}  (m  =  y1))  \mvee{}  ((n  =  y1)  \mwedge{}  (m  =  x1)))))
        {}\mRightarrow{}  ((y1  =  z)
              \mvee{}  (((x  =  y1)  \mwedge{}  (n  =  z))  \mvee{}  ((x  =  z)  \mwedge{}  (n  =  y1)))
              \mvee{}  (((y  =  y1)  \mwedge{}  (m  =  z))  \mvee{}  ((y  =  z)  \mwedge{}  (m  =  y1)))
              \mvee{}  ((x  =  y)  \mwedge{}  (((n  =  y1)  \mwedge{}  (m  =  z))  \mvee{}  ((n  =  z)  \mwedge{}  (m  =  y1)))))
        {}\mRightarrow{}  ((x1  =  z)
              \mvee{}  (((x  =  x1)  \mwedge{}  (n  =  z))  \mvee{}  ((x  =  z)  \mwedge{}  (n  =  x1)))
              \mvee{}  (((y  =  x1)  \mwedge{}  (m  =  z))  \mvee{}  ((y  =  z)  \mwedge{}  (m  =  x1)))
              \mvee{}  ((x  =  y)  \mwedge{}  (((n  =  x1)  \mwedge{}  (m  =  z))  \mvee{}  ((n  =  z)  \mwedge{}  (m  =  x1))))))
By
Latex:
((Auto  THEN  SplitOrHyps  THEN  ExRepD  THEN  SplitOrHyps  THEN  ExRepD)
  THEN  Try  (((OrLeft  THENM  Eq)  THEN  Auto))
  THEN  OrRight
  THEN  Auto)
Home
Index